Encyclopedia Brown and the case of the disgusting sneakers - Sobol, Donald J., 1924-; Owens, Gail (New York : Bantam, 1993)
America's Sherlock Holmes in sneakers continues his war on crime in ten more cases, the solutions to which are found in the back of the book.
4.4
3-6
3-6
School Library Journal
Booklist
Keywords: Mystery and detective stories; Literary recreations; Mystery fiction; Literary recreations